The hematopoietic stem cell niche: from embryo to adult - Gao, Xin (Development, 2018)
Hematopoietic stem cells (HSCs) develop in discrete anatomical niches, migrating during embryogenesis from the aorta-gonad-mesonephros (AGM) region to the fetal liver, and finally to the bone marrow, where most HSCs reside throughout adult life. These niches provide supportive microenvironments that specify, expand and maintain HSCs. Understanding the constituents and molecular regulation of HSC niches is of considerable importance as it could shed new light on the mechanistic principles of HSC emergence and maintenance, and provide novel strategies for regenerative medicine. However, controversy exists concerning the cellular complexity of the bone marrow niche, and our understanding of the different HSC niches during development remains limited. In this Review, we summarize and discuss what is known about the heterogeneity of the HSC niches at distinct stages of their ontogeny, from the embryo to the adult bone marrow, drawing predominantly on data from mouse studies.